The use of electromagnetic stirring of steel during the casting diameter 150 mm - Касьян, Г.І.; Козлова, З.Л.; Кучаєв, О.А.; Якобше, Р.Я. (Proceedings of National Aviation University (archive), 2008)
Investigation of travelling magnetic field effect in mold of six strand continuous caster on structure of 150 mm round bullet from low carbon steel are carried out. It is shown that increasing phase current of electromagnetic stirrer installed around of mold is extended the equiaxed crystals zone and is decreased billet axial porosity.